Proceedings Fourth International Conference on Tools With Artificial Intelligence TAI '92
DOI: 10.1109/tai.1992.246402
|View full text |Cite
|
Sign up to set email alerts
|

Genetic algorithms as a tool for feature selection in machine learning

Abstract: This paper describes an approach being explored to improve the usefulness of machine learning techniques for generating classification rules for complex, real world data. The approach involves the use of genetic algorithms as a 'Ifront e n d to traditional rule induction systems in order to identify and select the best subset of features to be used by the rule induction system. This approach has been implemented and tested on difJicult texture classification problems. The results are encouraging and indicate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
102
0

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(102 citation statements)
references
References 1 publication
0
102
0
Order By: Relevance
“…This method reduces the computational complexity and achieves better performing clustering [13]. Haleh Vafaie et al presented a genetic algorithm-based approach to develop the rules for identifying the suitable variable subset for the texture classification tasks and observed that it also can be used in rule induction machine learning systems [14]. W. Siedlecki et al presented the usage of the genetic algorithm for selecting the necessary feature subsets form the large dataset [15].…”
Section: Related Workmentioning
confidence: 99%
“…This method reduces the computational complexity and achieves better performing clustering [13]. Haleh Vafaie et al presented a genetic algorithm-based approach to develop the rules for identifying the suitable variable subset for the texture classification tasks and observed that it also can be used in rule induction machine learning systems [14]. W. Siedlecki et al presented the usage of the genetic algorithm for selecting the necessary feature subsets form the large dataset [15].…”
Section: Related Workmentioning
confidence: 99%
“…Over the years GA which is considered to be an inductive searching technique demonstrated substantial improvement [14]. The Feature selection using genetic algorithms are considered to be an excellent choice for improving the performance of the classification system [15]. The selection of an appropriate representation and an adequate evaluation function is vital for the successful implementation of any searching problem using GA. For the problem of feature selection the importance of selecting the appropriate representation and evaluation function is described in [16].…”
Section: Genetic Algorithmmentioning
confidence: 99%
“…When chromosome[i] is 1, the i th feature is selected for classification, and when it is 0, the i th feature is not selected [11,16].…”
Section: B Feature Selection Using Gamentioning
confidence: 99%
“…A mong the many methods proposed for feature selection, evolutionary optimization algorith ms such as genetic algorith m (GA) have gained a lot of attention. Genetic algorith m has been used as an efficient feature selection method in many applications [11,16].…”
Section: Introductionmentioning
confidence: 99%